Introduction of ultra-high-field MR brain imaging in infants: vital parameters, temperature and comfort - van Ooijen, I.M.; Annink, K.V.; Benders, M.J.N.L.; Dudink, J.; Alderliesten, T.; Groenendaal, F.; Tataranno, M.L.; Lequin, M.H.; Hoogduin, J.M.; Visser, F.; Raaijmakers, A.J.E.; Klomp, D.W.J.; et al. (Neuroimage. Reports, 2023)
Brain MRI in infants at ultra-high-field scanners might improve diagnostic quality, but safety should be evaluated first. In our previous study, we reported simulated specific absorption rates and acoustic noise data at 7 Tesla. In this study, we included twenty infants between term-equivalent age and three months of age. The infants were scanned on a 7 Tesla MRI directly after their clinically indicated 3 Tesla brain MRI scan. Vital parameters, temperature, and comfort were monitored throughout the process. Brain temperature was estimated during the MRI scans using proton MR spectroscopy. We found no significant differences in vital parameters, temperature, and comfort during and after 7 Tesla MRI scans, compared to 3 Tesla MRI scans. These data confirm our hypothesis that scanning infants at 7 Tesla MRI appears to be safe and we identified no additional risks from scanning at 3 Tesla MRI. •There was no difference in vital parameters, temperature, and comfort in infants between 3 T and 7 T MRI.•Scanning infants at 7 T MRI appears to be safe.•Future research should elucidate the advantages of 7T compared to 3T MRI, possibly improving diagnostic quality.